Characteristics of Laboratory Confirmed Ethylene Glycol and Methanol Exposures Reported to a Regional Poison Control Center - Tung, Robert C.; Thornton, Stephen L. (Kansas Journal of Medicine, 2019)
Introduction. Ethylene glycol (EG) and methanol (MET) exposuresare rare but can cause significant morbidity and mortality.Though frequently treated similarly, EG and MET exposures havecharacteristics that are not well differentiated in the literature. Wesought to describe the clinical characteristics of EG and MET exposures,confirmed with quantitative serum levels.Methods. An IRB-approved retrospective review of the Universityof Kansas Health System Poison Control Center database from July2005 to July 2015 identified all EG/MET exposures evaluated ata health care facility. Initial measurements were EG/MET levels,serum pH, serum creatinine, anion gap, serum ethanol level, maxanion gap, max osmolar gap, therapy performed (hemodialysis,fomepizole, ethanol) and death.Results. The search identified 75 cases, with 59 cases having onlydetectable EG levels and 15 cases having only detectable MET levels.The average EG level was 126 mg/dL (range 5 - 834). The averagedetectable methanol level was 78 mg/dL (range 5 - 396). The averagemaximum anion gap of the EG positive group was 20 mEq/L (range8 - 35). The average maximum anion gap of the MET positive groupwas 14 mEq/L (range 6 - 34). One death was reported in the EG positivegroup, with an initial level of 266 mg/dL.Conclusions. In this study of EG/MET exposures, EG exposureswere more common than MET exposures, but they had similardemographics, laboratory findings, and interventions. Continuedstudies are warranted to characterize these uncommon exposuresfurther. Kans J Med 2018;11(3):67-69.